Blockade of high-mobility group box 1 attenuates intestinal mucosal barrier dysfunction in experimental acute pancreatitis - Xia Chen (Nature Portfolio, 2017)
Abstract The release of inflammatory cytokines, that plays a dominant role in local pancreatic inflammation and systemic complications in severe acute pancreatitis (SAP). High-mobility group box 1 (HMGB1) is implicated in the mechanism of organ dysfunction and bacterial translocation in SAP. This current study aims to investigate possible role of HMGB1 in the intestinal mucosal barrier dysfunction of SAP, and the effect of anti-HMGB1 antibody treatment in intestinal mucosal injury in SAP. Our data revealed that the HMGB1 expression was significantly increased in AP mice induced by caerulein and LPS, and the inhibition of HMGB1 played a protective role in intestinal mucosal barrier dysfunction, reduced the serum level of other proinflammatory cytokines include IL-1β, IL-6, TNF-α. Next we investigated the downstream receptors involving in HMGB1 signaling. We found that the expressions of toll-like receptor (TLR) 4 and TLR9 were elevated in ileum of AP mice, the administration of HMGB1 neutralizing antibody significantly reduced the TLR4 and TLR9 expression. It was concluded that HMGB1 contributed the mechanism to the intestinal mucosal barrier dysfunction during AP. Blockade of HMGB1 by administration of HMGB1 neutralizing antibody may be a beneficial therapeutic strategy in improving intestinal mucosal barrier dysfunction in SAP.